The Influence Of Search Engine Student's Conduct In Junior High School Country Pancur Batu District - Daryanto Setiawan; Ahmad Tamrin Sikumbang; Yusnadi Yusnadi (LPPPIPublishing, 2022)
Research this start because of existence the anxiety that happened moment it's on morality student, a goal for uncovering influence search engine against akhlah students at Junior High School State in the District Stone Shower. Method research used is field research with data collection techniques using questionnaires as well. There are 30 respondents in the study. Research results show that (1). There is a direct effect of the use of social media on the use of student search engine Junior High School State in the District Stone Shower of 0.518 with a t - count coefficient of 10,457, which is greater than the value of t table a(0.05) = 1.97 and a(0.01 ) = 2.59. This thing means the more often use social media so will the more take effect to use the student search engine Junior High School State in the District Stone Shower. (2). There is a direct effect of a useful search engine on morality student Junior High School Country in Sub-District Stone Shower of 0.162 with a t-count coefficient of 2.609, greater than the value of t table a(0.05) = 1.97 and a(0.01 ) = 2.59. This thing means the more often use search engines so will the more takes effect on the morals of students in Junior High School State in the District Stone Shower.